Social isolation, inflammation, and cancer mortality from the National Health and Nutrition Examination Survey - a study of 3,360 women - Alexander Koh-Bell; Joshua Chan; Amandeep K. Mann; Daniel S. Kapp (BMC, 2021)
Abstract Background This study evaluates the role of social isolation on inflammation and cancer mortality among women. Methods Data were abstracted from the U.S. National Health and Nutrition Examination Survey from 1988 to 1994. The Social Network Index was used to assess participants' degree of social isolation. C-reactive protein and fibrinogen levels were included as markers of inflammation. We used the National Death Index to identify causes and dates of mortality. Chi-square and multivariable Cox regressions were employed for statistical analyses. Results Of 3360 women (median age: 54 years), the most isolated, very isolated, somewhat isolated, and not isolated comprised 14.5, 30.2, 37.1, and 18.2% of the sample, respectively. The most isolated participants were more likely to have low income (56.8% vs 12.2%, p < 0.001), have fewer years of education (40.8% vs 12.3%; p < 0.001), have low physical activity (27.3% vs 14.7%; p < 0.003), be obese (32.5% vs 24.4%; p = 0.02), and be current smokers (34.2% vs 10.3%; p < 0.001) compared to the not isolated ones. Mean fibrinogen levels increased with degree of social isolation (p = 0.003), but C-reactive protein showed no association (p = 0.52). Kaplan-Meier estimates indicated higher cancer mortality rates among participants with elevated fibrinogen levels, though not with statistical significance (p = 0.08). Furthermore, there was no association between social isolation and cancer mortality (p = 0.54). On multivariate analysis, obesity (HR = 1.56; 95% CI: 1.11-2.18), higher education (HR = 1.36; 95% CI: 1.01-1.83), and smoking (HR = 4.42, 95% CI: 2.84-6.88) were independent predictors for cancer mortality, while high physical activity predicted for lower mortality from cancer (HR = 0.67, 95% CI: 0.51-0.87). However, social isolation was not a predictor. Conclusion Social isolation among women was associated with an increased level of fibrinogen, but not associated with cancer mortality. The relationship between inflammation and cancer mortality warrants further investigation.